Composite cross-linked polyacrylamide corrosion inhibitor as well as preparation method and application thereof

By using composite crosslinked polyacrylamide corrosion inhibitors, combined with organic and inorganic composite crosslinking and benzotriazole components, the problem of corrosion inhibitor degradation under high temperature conditions is solved, and efficient corrosion resistance is achieved. Long-term protection of equipment.

CN119431832APending Publication Date: 2025-02-14CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310941589.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Under high temperature conditions, existing corrosion inhibitors are prone to degradation and cannot continue to provide long-term effective protection for oil and gas field equipment, resulting in more susceptibility to corrosion of the equipment.

Method used

The corrosion inhibitor of composite crosslinked polyacrylamide is used to significantly improve the sustained release effect under high temperature conditions through organic and inorganic crosslinking, and the addition of benzotriazole corrosion inhibiting components.

Benefits of technology

It significantly improves the sustained release effect of corrosion inhibitors at high temperatures, extends the service life of the equipment, and improves the economic benefits of high-temperature oil and gas fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119431832A_ABST
    Figure CN119431832A_ABST
Patent Text Reader

Abstract

The invention provides a composite cross-linked polyacrylamide corrosion inhibitor as well as a preparation method and application thereof, and the preparation method of the composite cross-linked polyacrylamide corrosion inhibitor comprises the following steps: (1) carrying out first reaction on polyacrylamide and 3-hydroxybenzotriazole under the action of a first catalyst to obtain a first reactant; and (2) mixing an inorganic chromium salt, resin and the first reactant to obtain a corrosion inhibition composition, and carrying out a second reaction on the corrosion inhibition composition in a target stratum environment to obtain the composite cross-linked polyacrylamide corrosion inhibitor. By adopting an organic-inorganic composite cross-linking method and adding the benzotriazole corrosion inhibition component, the high-temperature-resistant corrosion inhibitor has a high-temperature-resistant effect, can be applied in a high-temperature oil reservoir environment, has a good slow-release effect and further improves the benefits of high-temperature oil reservoir development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemical additives, and in particular to a composite cross-linked polyacrylamide corrosion inhibitor and a preparation method and application thereof. Background Art

[0002] The exploitation of most oil fields has entered the middle and late stages of water drive or chemical drive development. The free oxygen in the produced fluid is very easy to cause corrosion under high temperature. After enrichment and scaling, it will cause serious corrosion to the oil production equipment, making it impossible for the oil production equipment and gathering and transportation equipment to operate effectively and normally.

[0003] At present, the main anti-corrosion measures used by domestic and foreign oil and gas fields to solve corrosion problems include: corrosion inhibitors, deoxidizers, cathodic protection, coating protection, nitriding protection and FRP pipes, etc. Among them, the corrosion inhibitor method has the advantages of high economic benefits, strong adaptability, high efficiency, simple operation and good safety, and has received widespread attention.

[0004] The factors that cause corrosion in oil and gas fields are relatively complex. The main factors include: temperature, pH value, corrosive gas, mineralization, flow rate and water content, among which the corrosion rate of metals is deeply affected by temperature. In some corrosive environments, increasing the temperature may lead to changes in the corrosion mechanism. For example, in an oxygen-containing corrosive environment, the corrosion products obtained under different temperature conditions are different. Due to the different adsorption effects of different corrosion products on the metal surface, the formed corrosion product film has different protective effects on the metal surface, which affects the corrosion rate.

[0005] Generally speaking, the higher the temperature, the more difficult it is to prevent corrosion, especially for oil and gas fields that use corrosion inhibitors as the main means of corrosion prevention. This is because most corrosion inhibitors are prone to degradation under high temperature conditions and cannot continuously provide long-term and effective protection for equipment materials, making the equipment more susceptible to corrosion under high temperature conditions.

[0006] Therefore, developing a high-temperature resistant corrosion inhibitor is of great significance for further improving the economic benefits of high-temperature oil and gas fields. Summary of the invention

[0007] In view of the problems existing in the prior art, the present invention provides a composite cross-linked polyacrylamide corrosion inhibitor and a preparation method and application thereof. By adopting organic and inorganic composite cross-linking and adding benzotriazole corrosion inhibition components, the sustained-release effect of the corrosion inhibitor under high temperature conditions is significantly improved, solving the problem of high-temperature oil reservoir corrosion.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a composite cross-linked polyacrylamide corrosion inhibitor, the molecular formula of the corrosion inhibitor is shown in formula (1):

[0010]

[0011] In formula (1), the value range of x is 500-2000, the value range of y is 1000-3000, the value range of z is 500-2000, and the value range of n is 10-100.

[0012] The corrosion inhibitor provided by the present invention contains polyacrylamide fragments, which have a slow-release effect; and also contains phenolic resin fragments, which are cross-linked with polyacrylamide and compositely cross-linked through chromium ions, so that a better protective film layer can be formed on the surface of the tool. In addition, 3-hydroxybenzotriazole is added to have a drag-reducing effect, and the corrosion resistance at high temperature is significantly improved.

[0013] Since the requirements for corrosion inhibitors in oil reservoirs are relatively high, on the one hand, it is required that after the corrosion inhibitor is formed, it can form a stable protective film on the surface of the tool to play an anti-corrosion effect; on the other hand, once the corrosion inhibitor is formed, it is a gel-like substance, which is difficult to transport using a pump. Therefore, it is expected that the raw materials for forming the corrosion inhibitor will be transported to the oil reservoir before the corrosion inhibitor is formed on the surface of the tool. However, the cross-linking effect of divalent metal ions is obviously not as good as that of trivalent ions, which can easily lead to dehydration of the corrosion inhibitor and fail to achieve the effect of corrosion protection. Therefore, trivalent metal ions are selected, and the cross-linking speed of iron ions is relatively fast, resulting in cross-linking before the raw materials are transported to the oil reservoir, and it is impossible to form a protective film on the surface of the equipment or cause the problem of being unable to transport by pump pressure; although zirconium and / or aluminum ions can form a cross-linking effect, the gel system formed by these two metal ions is weak and has a low viscosity. The protective film formed is difficult to withstand high temperatures and has poor corrosion resistance at high temperatures. Through various studies and experiments, the present invention has found that Cr ions have excellent cross-linking effects, the gel system formed is strong, can play an excellent protective role and has strong high temperature resistance, and has a delayed reaction effect, and can form a corrosion inhibitor film layer on the surface of tools and equipment after the raw materials are transported to the oil reservoir.

[0014] The value range of x is 500 to 2000, for example, it can be 500, 660, 830, 1000, 1160, 1330, 1500, 1660, 1830 or 2000, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0015] The value range of y is 1000 to 3000, for example, it can be 1000, 1220, 1440, 1600, 1800, 2110, 2330, 2550, 2770 or 3000, but is not limited to the listed values, and other values ​​not listed in the range are also applicable.

[0016] The value range of z is 500 to 2000, for example, it can be 500, 660, 830, 1000, 1160, 1330, 1500, 1660, 1830 or 2000, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0017] The value range of n is 10 to 100, for example, it can be 10, 20, 30, 40, 50, 60, 70, 80, 90 or 100, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0018] The present invention is more conducive to obtaining a suitable cross-linked corrosion inhibitor by controlling the range of x, y, z and n within the above range. The viscosity range is more suitable, which is 50 to 200 mPa·s, and the viscosity is preferably controlled between 100 and 150 mPa·s, which has a better corrosion inhibition effect.

[0019] Preferably, the value range of x is 600-1200, the value range of y is 1200-2000, the value range of z is 1000-1500, and the value range of n is 20-30.

[0020] In a second aspect, the present invention provides a method for preparing the composite cross-linked polyacrylamide corrosion inhibitor according to the first aspect, the preparation method comprising:

[0021] (1) polyacrylamide and 3-hydroxybenzotriazole undergo a first reaction under the action of a first catalyst to obtain a first reactant;

[0022] (2) Mixing an inorganic chromium salt, a resin and the first reactant to obtain a corrosion-inhibiting composition, wherein the corrosion-inhibiting composition undergoes a second reaction under a target formation environment to obtain a composite cross-linked polyacrylamide-based corrosion inhibitor.

[0023] The present invention first prepares a first reactant, uses 3-hydroxybenzotriazole to modify polyacrylamide, and then mixes an inorganic chromium salt, a resin and the first reactant and introduces them into an oil reservoir to cause a second reaction to form a corrosion inhibitor. The corrosion inhibitor composition undergoes a second reaction in situ under a target formation environment to directly form a polymer protective layer on the surface of the equipment. On the one hand, the bonding strength with the surface of the equipment is higher, and on the other hand, the corrosion inhibitor formed in situ has an excellent corrosion inhibition effect and improves the high-temperature corrosion inhibition rate.

[0024] Preferably, the mass ratio of polyacrylamide to 3-hydroxybenzotriazole in step (1) is (5-10):(10-20), the number of parts of polyacrylamide can be, for example, 5, 6, 7, 8, 9 or 10, and the number of parts of 3-hydroxybenzotriazole can be, for example, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20, etc.

[0025] In the present invention, the mass ratio of polyacrylamide and 3-hydroxybenzotriazole is preferably within the above range. When the content of polyacrylamide is too high, there is a problem of excessive crosslinking and reduced fit with the equipment surface. When the content of polyacrylamide is too low, there is insufficient crosslinking, reduced viscosity and reduced temperature resistance. When the content of 3-hydroxybenzotriazole is too high, the corrosion inhibitor is dehydrated at high temperature. After dehydration, half of the corrosion inhibitor is solid phase and half is water phase, which makes it difficult to play a protective role. When the content of 3-hydroxybenzotriazole is too low, it is difficult to play a drag reduction role.

[0026] Preferably, the mass ratio of the first catalyst to polyacrylamide is (1-2):(5-10), the number of parts of the first catalyst can be, for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0, etc., and the number of parts of polyacrylamide can be, for example, 5, 6, 7, 8, 9 or 10, etc.

[0027] Preferably, in step (1), the first catalyst is thiourea.

[0028] Preferably, the temperature of the first reaction is 45-55°C, for example, it can be 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 51°C, 52°C, 53°C, 54°C or 55°C.

[0029] Preferably, the first reaction time is 3 to 5 h, for example, 3 h, 3.1 h, 3.2 h, 3.5 h, 3.8 h, 4.0 h, 4.2 h, 4.5 h, 4.8 h or 5 h.

[0030] Preferably, the order of mixing materials for the first reaction in step (1) includes: first dissolving the first catalyst in water, then adding polyacrylamide and aging to obtain a polyacrylamide base liquid, and then mixing 3-hydroxybenzotriazole and the polyacrylamide base liquid.

[0031] Preferably, the aging temperature is room temperature.

[0032] Preferably, the aging time is 20 to 28 hours, for example, it can be 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, 26 hours, 27 hours or 28 hours.

[0033] Preferably, the mass ratio of the first catalyst to water is (1-2):(56-78), the number of parts of the first catalyst can be, for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0, and the number of parts of water can be, for example, 56, 58, 60, 62, 63, 65, 68, 69, 70, 72, 75 or 78, etc.

[0034] Preferably, the mass ratio of the inorganic chromium salt in step (2) to the polyacrylamide in step (1) is (1-2):(5-10), the number of parts of the inorganic chromium salt can be, for example, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9 or 2.0, and the number of parts of the polyacrylamide can be, for example, 5, 6, 7, 8, 9 or 10.

[0035] When the content of the inorganic chromium salt is too high, the salinity is too high, which easily leads to dehydration of the corrosion inhibitor. When the content of the inorganic chromium salt is too low, the cross-linking degree is insufficient, which makes it difficult to achieve the effect of high temperature resistance.

[0036] Preferably, the mass ratio of the resin in step (2) to the polyacrylamide in step (1) is (5-10):(5-10), the number of parts of the resin can be, for example, 5, 6, 7, 8, 9 or 10, and the number of parts of the polyacrylamide can be, for example, 5, 6, 7, 8, 9 or 10.

[0037] In the present invention, when the resin content is too high, the phenolic resin cannot be fully cross-linked, resulting in the formation of phenolic resin precipitation. When it is too low, the composite cross-linking is insufficient, resulting in insufficient overall temperature resistance of the system.

[0038] The above mass ratios of the present invention can be arbitrarily proportioned according to the numbers listed, or can be proportioned using values ​​within other ranges not listed.

[0039] Preferably, the inorganic chromium salt is chromium chloride.

[0040] Preferably, the resin is a phenolic resin.

[0041] Preferably, the temperature of the second reaction is 80-230°C, for example, it can be 80°C, 90°C, 100°C, 120°C, 130°C, 140°C, 150°C, 170°C, 180°C, 200°C, 210°C, 220°C or 230°C, etc.

[0042] As a preferred technical solution of the second aspect of the present invention, the preparation method comprises:

[0043] (1) First, 1 to 2 parts of thiourea are dissolved in 56 to 78 parts of water, and then 5 to 10 parts of polyacrylamide are slowly added, and the mixture is aged at room temperature (25° C.) for 20 to 28 hours to obtain a polyacrylamide base liquid, and then 10 to 20 parts of 3-hydroxybenzotriazole and the polyacrylamide base liquid are mixed, and a first reaction is carried out at 45 to 55° C. for 3 to 5 hours to obtain a first reactant;

[0044] (2) Mixing 1 to 2 parts of chromium chloride, 5 to 10 parts of phenolic resin and the first reactant to obtain a corrosion inhibition composition, wherein the corrosion inhibition composition undergoes a second reaction under a target formation environment of 80 to 230° C. to obtain a composite cross-linked polyacrylamide corrosion inhibitor.

[0045] The preparation method of the corrosion inhibitor provided by the present invention is to first prepare a polymer of polyacrylamide and 3-hydroxybenzotriazole, as shown in the following equation:

[0046]

[0047] Then the polymer, inorganic chromium salt and resin are mixed to cause inorganic crosslinking reaction and organic crosslinking reaction. There is no order of precedence between the inorganic crosslinking reaction and the organic crosslinking reaction. They can be carried out simultaneously or one can be carried out first and then the other. The equation for carrying out the inorganic crosslinking reaction first is:

[0048]

[0049] The equation for the organic cross-linking reaction is:

[0050]

[0051] In a third aspect, the present invention provides a use of the composite cross-linked polyacrylamide corrosion inhibitor described in the first aspect in an oil reservoir.

[0052] The corrosion inhibitor prepared by the invention has excellent performance and a wide source of raw materials, and can be widely used in oil reservoirs to protect oil reservoir equipment from corrosion.

[0053] Preferably, the corrosion inhibitor provided by the present invention preferably acts together with polyacrylamide when used to achieve a better drag reduction effect in the oil reservoir.

[0054] Preferably, the oil reservoir is a high-temperature oil reservoir environment, and the high temperature ranges from 80 to 230°C, for example, it can be 80°C, 90°C, 100°C, 120°C, 130°C, 140°C, 150°C, 170°C, 180°C, 200°C, 210°C, 220°C or 230°C, etc.

[0055] The present invention has no special requirements on the material of the oil reservoir equipment. The corrosion inhibitor provided by the present invention can be applied to any equipment in the oil reservoir equipment that needs to be anti-corrosive, for example, it can be made of stainless steel or other materials.

[0056] The present invention has no special requirements on other performance parameters of the oil reservoir, and any performance parameters of the oil reservoir known to those skilled in the art may be adopted.

[0057] Compared with the prior art, the present invention has at least the following beneficial effects:

[0058] (1) The composite cross-linked polyacrylamide corrosion inhibitor provided by the present invention contains polyacrylamide, has better water solubility, and still has a good corrosion inhibition rate at 230°C, which can reach more than 76%, preferably more than 80%, and even more than 84%;

[0059] (2) The preparation method of the composite cross-linked polyacrylamide corrosion inhibitor provided by the present invention has a simple process, a wide source of raw materials and low cost;

[0060] (3) The composite cross-linked polyacrylamide corrosion inhibitor provided by the present invention can be well applied in high-temperature oil reservoirs, thereby avoiding corrosion of equipment under high-temperature oil reservoir conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 It is a picture showing the effect of the corrosion inhibitor in Example 1 of the present invention before and after the corrosion test.

[0062] Figure 2 These are the effect diagrams before and after the corrosion test without adding corrosion inhibitor in the present invention. DETAILED DESCRIPTION

[0063] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0064] The present invention is further described in detail below. However, the following examples are only simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention shall be subject to the claims.

[0065] Example 1

[0066] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, the structural formula of the composite cross-linked polyacrylamide corrosion inhibitor is shown in the following formula (1):

[0067]

[0068] In formula (1), x is 600, y is 1200, z is 1400, and n is 20.

[0069] This embodiment also provides a method for preparing the composite cross-linked polyacrylamide corrosion inhibitor, which comprises the following steps:

[0070] (1) First, 1 part of thiourea is dissolved in 78 parts of water, and then 5 parts of polyacrylamide is slowly added to fully dissolve it, and then aged at room temperature (25° C.) for 24 hours to obtain a polyacrylamide base liquid, and then 10 parts of 3-hydroxybenzotriazole and the polyacrylamide base liquid are mixed, and a first reaction is carried out at 50° C. for 4 hours to obtain a first reactant;

[0071] (2) Mixing 1 part of chromium chloride, 5 parts of phenolic resin (brand: phenolic resin 2123) and the first reactant to obtain a corrosion inhibition composition, wherein the corrosion inhibition composition undergoes a second reaction under the target formation environment to obtain a composite cross-linked polyacrylamide corrosion inhibitor.

[0072] The effect of the corrosion inhibitor provided in this embodiment before and after corrosion at 230°C is as follows Figure 1 As shown, Figure 1 The top is before corrosion. Figure 1 The following is after corrosion, and Figure 2 This is a comparison chart without adding corrosion inhibitor. Figure 2 The top is before corrosion, the bottom is after corrosion, Figure 1 and Figure 2 It can be seen that the corrosion inhibitor provided in this embodiment has an excellent corrosion inhibition effect and significantly improves the corrosion resistance of the equipment at high temperatures.

[0073] Example 2

[0074] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, the structural formula of the composite cross-linked polyacrylamide corrosion inhibitor is shown in the following formula (1):

[0075]

[0076] In formula (1), x is 800, y is 1300, z is 1200, and n is 25.

[0077] This embodiment also provides a method for preparing the composite cross-linked polyacrylamide corrosion inhibitor, which comprises the following steps:

[0078] (1) First, 2 parts of thiourea are dissolved in 58 parts of water, and then 10 parts of polyacrylamide are slowly added to fully dissolve it, and then aged at room temperature (25° C.) for 28 hours to obtain a polyacrylamide base liquid, and then 15 parts of 3-hydroxybenzotriazole and the polyacrylamide base liquid are mixed, and a first reaction is carried out at 45° C. for 5 hours to obtain a first reactant;

[0079] (2) Mixing 1.5 parts of chromium chloride, 8 parts of phenolic resin (brand: phenolic resin 2123) and the first reactant to obtain a corrosion inhibition composition, wherein the corrosion inhibition composition undergoes a second reaction under the target formation environment to obtain a composite cross-linked polyacrylamide corrosion inhibitor.

[0080] Example 3

[0081] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, the structural formula of the composite cross-linked polyacrylamide corrosion inhibitor is shown in the following formula (1):

[0082]

[0083] In formula (1), x is 1200, y is 1800, z is 1500, and n is 27.

[0084] This embodiment also provides a method for preparing the composite cross-linked polyacrylamide corrosion inhibitor, which comprises the following steps:

[0085] (1) First, 1.5 parts of thiourea are dissolved in 70 parts of water, and then 8 parts of polyacrylamide are slowly added to fully dissolve it, and then aged at room temperature (25° C.) for 20 hours to obtain a polyacrylamide base liquid, and then 10 parts of 3-hydroxybenzotriazole and the polyacrylamide base liquid are mixed, and a first reaction is carried out at 55° C. for 3 hours to obtain a first reactant;

[0086] (2) Mixing 2 parts of chromium chloride, 10 parts of phenolic resin (brand: phenolic resin 2123) and the first reactant to obtain a corrosion inhibition composition, wherein the corrosion inhibition composition undergoes a second reaction under the target formation environment to obtain a composite cross-linked polyacrylamide corrosion inhibitor.

[0087] Example 4

[0088] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, which is the same as that of Embodiment 1 except that the polyacrylamide in the preparation method is replaced by 2 parts instead of 5 parts, and will not be described in detail here.

[0089] In this embodiment, the viscosity of the corrosion inhibitor is too low, and the system does not have good temperature and shear resistance.

[0090] Example 5

[0091] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, which is the same as that of Embodiment 1 except that the polyacrylamide in the preparation method is replaced by 15 parts instead of 5 parts, and will not be described in detail here.

[0092] The viscosity of the corrosion inhibitor in this embodiment is too high, making the system difficult to flow.

[0093] Example 6

[0094] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, which is the same as that of Example 1 except that 3-hydroxybenzotriazole in the preparation method is replaced by 5 parts instead of 10 parts. The slow-release performance of this embodiment is lower than that of Example 1.

[0095] Example 7

[0096] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, which is the same as that of embodiment 1 except that 3-hydroxybenzotriazole is replaced by 25 parts instead of 10 parts, and will not be described in detail here. The cost of this embodiment is too high.

[0097] Example 8

[0098] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, which is the same as that in Example 1 except that chromium chloride is replaced by 5 parts instead of 1 part, and will not be described in detail here. In this embodiment, excessive cross-linking causes the system to be prone to water separation.

[0099] Example 9

[0100] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, which is the same as that in Embodiment 1 except that chromium chloride is replaced by 0.2 parts instead of 1 parts, and is not described in detail here. In this embodiment, the system has insufficient cross-linking performance, resulting in easy degradation of the system.

[0101] Example 10

[0102] This embodiment provides a composite cross-linked polyacrylamide corrosion inhibitor, which is the same as that of Embodiment 1 except that chromium chloride is replaced by chromium nitrate, and will not be described in detail here.

[0103] Comparative Example 1

[0104] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that step (2) is not performed, that is, the first reactant is directly used as the corrosion inhibitor, and the rest is not repeated here.

[0105] This comparative example cannot be used as a corrosion inhibitor and has no corrosion inhibition effect.

[0106] Comparative Example 2

[0107] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that the phenolic resin is replaced by hexamethylenetetramine, and is not described in detail here.

[0108] Comparative Example 3

[0109] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that chromium chloride is replaced by ferric chloride, and will not be described in detail here.

[0110] Comparative Example 4

[0111] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that chromium chloride is replaced by zirconium chloride, and is not described again.

[0112] Comparative Example 5

[0113] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that chromium chloride is replaced by aluminum chloride, and will not be described again.

[0114] Comparative Example 6

[0115] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that 3-hydroxybenzotriazole is replaced by 1-carboxybenzotriazole, and is not described again.

[0116] Comparative Example 7

[0117] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that chromium chloride is not added in step (2), and will not be described in detail here.

[0118] Comparative Example 8

[0119] This comparative example provides a corrosion inhibitor, which is the same as Example 1 except that no phenolic resin is added in step (2), and will not be described in detail here.

[0120] Test method: The method described in GB / T35509-2017 Application and Evaluation of Corrosion Inhibitors in Oil and Gas Fields was used, and the corrosion inhibition rate was analyzed at 230°C using the hanging plate method.

[0121] The test results of the above embodiments and comparative examples are shown in Table 1.

[0122] Table 1

[0123]

[0124] In Table 1, “ / ” means there is no relevant data or no special remarks are required.

[0125] From Table 1, we can see the following points:

[0126] (1) It can be seen from Examples 1 to 3 that the composite cross-linked polyacrylamide corrosion inhibitor provided by the present invention has excellent high-temperature corrosion resistance, wherein the viscosity of the corrosion inhibitor is controlled between 100 and 150 mPa·s, the performance is excellent, and the corrosion rate is ≤0.94 g / m at a high temperature of 230°C for 168 h. 2 ·h, the corrosion inhibition rate is above 76%.

[0127] (2) Comprehensive Example 1 and Comparative Examples 1 to 8 and no corrosion inhibitor can be seen that in Example 1, polyacrylamide, phenolic resin, 3-hydroxybenzotriazole and chromium chloride are used for crosslinking. Compared with the changes in the crosslinking materials in Comparative Examples 1 to 8, the corrosion inhibition rate in Example 1 is as high as 84.39%, while in Comparative Example 1, the first reactant is directly used as a corrosion inhibitor, which is difficult to achieve a corrosion inhibition effect, and the corrosion inhibition rate is only 0.76%; in Comparative Example 2, only the phenolic resin is replaced by hexamethylenetetramine, which can also play a crosslinking role, but the corrosion inhibitor strength after crosslinking is low and easy to dissolve, resulting in a high-temperature corrosion inhibition rate of only 9.04%; in Comparative Example 3, chromium ions are replaced by iron ions. Due to the excessively fast crosslinking of the iron ions, the chromium ions do not enter the oil reservoir. The corrosion inhibitor will be severely dehydrated, and the high-temperature corrosion inhibition rate is only 26.83%; zirconium ions are used in Comparative Example 4, which leads to too slow cross-linking, and it takes a long time to achieve cross-linking. The equipment corrodes in the oil reservoir, and the corrosion inhibition rate is only 8.47%; aluminum ions are used in Comparative Example 5. Although cross-linking can also occur, the cross-linking strength of aluminum ions is too low, and dehydration is prone to occur after cross-linking, and the high-temperature corrosion inhibition rate is only 57.85%; 1-carboxybenzotriazole is used in Comparative Example 6, and the corrosion inhibition performance is significantly lower than that of Example 1; chromium chloride is not added in Comparative Example 7, and the corrosion inhibition rate is only 5.23%, and there is almost no corrosion inhibition effect; phenolic resin is not added in Comparative Example 8, and the slow release rate is only 12.18%, which is extremely low. This shows that the combination and selection of the various substances in the present invention are very critical, and the components work together to significantly improve the corrosion inhibition effect;

[0128] (3) It can be seen from Example 1 and Examples 4 to 5 that the number of parts of polyacrylamide in Example 1 is 5 parts, compared with 2 parts and 15 parts in Examples 4 to 5 respectively. The corrosion inhibition rate in Example 1 is as high as 84.39%, while in Examples 4 to 5 it is only 44.53% and 12.08% respectively. This shows that the present invention significantly improves the corrosion inhibition performance of the corrosion inhibitor by optimizing the amount of polyacrylamide. A similar conclusion can be drawn by comparing Example 1 with Examples 6 to 9. The selection of the amount of chromium chloride and 3-hydroxybenzotriazole has a greater influence on improving the corrosion inhibition performance of the corrosion inhibitor.

[0129] (4) It can be seen from Example 1 and Example 10 that, compared with Example 10 in which chromium chloride is used for cross-linking, Example 1 has a better corrosion inhibition effect. In Example 10, due to the excessively fast cross-linking, the system is cross-linked prematurely, resulting in high viscosity on the ground and difficulty in injection, resulting in poor corrosion inhibition effect. This shows that the present invention significantly improves the corrosion inhibition effect and effectively controls the cross-linking speed by preferably using chromium chloride for cross-linking.

[0130] The present invention illustrates the detailed structural features of the present invention through the above embodiments, but the present invention is not limited to the above detailed structural features, that is, it does not mean that the present invention must rely on the above detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A composite cross-linked polyacrylamide corrosion inhibitor, characterized in that: The molecular formula of the corrosion inhibitor is shown in formula (1): In formula (1), the value range of x is 500-2000, the value range of y is 1000-3000, the value range of z is 500-2000, and the value range of n is 10-100.

2. The corrosion inhibitor according to claim 1, characterized in that The value range of x is 600 to 1200, the value range of y is 1200 to 2000, the value range of z is 1000 to 1500, and the value range of n is 20 to 30.

3. A method for preparing a composite cross-linked polyacrylamide corrosion inhibitor according to claim 1 or 2, characterized in that: The preparation method comprises: (1) polyacrylamide and 3-hydroxybenzotriazole undergo a first reaction under the action of a first catalyst to obtain a first reactant; (2) Mixing an inorganic chromium salt, a resin and the first reactant to obtain a corrosion-inhibiting composition, wherein the corrosion-inhibiting composition undergoes a second reaction under a target formation environment to obtain a composite cross-linked polyacrylamide-based corrosion inhibitor.

4. The preparation method according to claim 3, characterized in that: The mass ratio of polyacrylamide to 3-hydroxybenzotriazole in step (1) is (5-10):(10-20); Preferably, the mass ratio of the first catalyst to polyacrylamide is (1-2):(5-10).

5. The preparation method according to claim 3 or 4, characterized in that: In step (1), the first catalyst is thiourea; Preferably, the temperature of the first reaction is 45-55°C; Preferably, the first reaction time is 3 to 5 hours.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The order of mixing materials for the first reaction in step (1) includes: first dissolving the first catalyst in water, then adding polyacrylamide, and aging to obtain a polyacrylamide base liquid, and then mixing 3-hydroxybenzotriazole and the polyacrylamide base liquid; Preferably, the aging temperature is room temperature; Preferably, the aging time is 20 to 28 hours; Preferably, the mass ratio of the first catalyst to water is (1-2):(56-78).

7. The preparation method according to any one of claims 3 to 6, characterized in that: The mass ratio of the inorganic chromium salt in step (2) to the polyacrylamide in step (1) is (1-2):(5-10); Preferably, the mass ratio of the resin in step (2) to the polyacrylamide in step (1) is (5-10):(5-10); Preferably, the inorganic chromium salt is chromium chloride; Preferably, the resin is a phenolic resin.

8. The preparation method according to any one of claims 3 to 7, characterized in that: The temperature of the second reaction is 80-230°C.

9. Use of the composite cross-linked polyacrylamide corrosion inhibitor according to claim 1 or 2 in oil reservoirs.

10. The use according to claim 9, characterized in that: The oil reservoir is a high-temperature oil reservoir environment, and the high temperature ranges from 80 to 230°C.